Application of the Survey Question Read Recite and Review (SQ3R) Method to Students' Reading Comprehension Skills - Safitri, Lale Aprihatin Diana (Lembaga Yasin AlSys, 2025)
This study discusses how to improve students' reading skills through the Survey Question Read Recite and Review (SQ3R) method. The purpose of this study is to improve the reading skills of grade VII students, this is due to the lack of students' ability to understand the texts they read. The data source in this study was grade VII students of SMP ISLAM TERAMPIL NM NW APANCOR KOPONG with a total of 23 students. This study was conducted in two cycles and the data collected were quantitative and qualitative data. Quantitative data is data obtained from the results of formative tests in each cycle, while qualitative data is in the form of observation results in each learning cycle. Based on the results of the study, the application of the SQ3R method can improve students' reading comprehension skills. This can be seen from the results of the students' reading comprehension test before the action was taken which only achieved classical completeness of 42.30% or could be said to be lacking. After applying the method in cycle I, students' reading comprehension skills increased with classical completeness of 69.23%, this can be said to be sufficient. In cycle II, students' reading comprehension ability increased quite significantly, namely with classical completeness of 88.46%, which is considered perfect. Thus, it can be concluded that the application of the Survey, Question, Read, Recite and Review (SQ3R) method can improve the reading comprehension ability of grade VII students.